THE EFFECTIVENESS OF INTERACTIVE LEARNING MEDIA IN ENHANCING STUDENT LEARNING OUTCOMES: A SYSTEMATIC LITERATURE REVIEW - Ega Devianti; Robinson Situmorang; Mita Septiani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Interactive learning media has become crucial in Indonesian education, accelerated by COVID-19's digital transformation impact. This systematic review examines interactive media effectiveness in improving student learning outcomes in Indonesian educational contexts using PRISMA 2020 methodology. Twenty eligible articles were selected from several hundred studies through systematic PRISMA screening, analyzing e-modules, simulations, interactive videos, educational games, and AR/VR technologies across educational levels. All interactive media types showed significant positive impact with 20-35% average improvement versus conventional methods. Simulations and VR/AR demonstrated highest effectiveness. Success requires integrating three pillars: Technology × Pedagogy × Organization, expanding TPACK framework. Indonesian context faces unique challenges: infrastructure disparities, teacher readiness gaps, and policy coordination needs. Pedagogical design quality outweighs technological sophistication in determining effectiveness.